Constructing a continuous amorphous carbon interlayer to enhance dielectric performance of carbon nanotubes/polyvinylidene fluoride nanocomposites. (May 2017) - Yang, Minhao; Zhao, Hang; He, Delong; Bai, Jinbo
Abstract: Carbon nanotubes (CNTs) based percolative polymer nanocomposites own a high dielectric constant at a small amount of CNTs. However, CNTs are easy to connect with each other directly in the vicinity of percolation threshold ( f c ), which unavoidably leads to an abrupt increase in dielectric loss. Herein, we propose a facile way to fabricate core-shell structured CNTs@amorphous carbon (CNTs@AC) hybrids by chemical vapor deposition (CVD). The CNT@AC hybrids were subsequently integrated into polyvinylidene fluoride (PVDF) matrix to fabricate CNTs@AC/PVDF dielectric nanocomposites by the combination of solution casting and extrusion-injection procedures. The uniform AC shell provides an insulative interlayer for the adjacent CNTs, which not only hinders the direct contact of CNTs but also improves the dispersibility of CNTs in PVDF matrix. Compared with pristine CNTs (P-CNTs)/PVDF nanocomposites, the f c increases from 7.16 vol % to 11.81 vol % and the dielectric loss decreases from 83.66 to 1.35 for the CNTs@AC-60/PVDF nanocomposites, which indicates that the percolation behavior is delayed. The results indicate that the influence of AC interlayer on the dielectric performance of the nanocomposites after percolation is much more evident than that before percolation. All these results demonstrate that this strategy is effective to enhance the dielectric performance of polymer nanocomposites and the design concept could be extended to other carbon hybrids materials.